Enhanced 3D velocity structure, seismicity relocation and basement characterization of Changning shale gas and salt mining regions in southern Sichuan basin - Anyiam, Uzonna Okenna; Zhang, Haijiang; Tan, Yuyang; Qian, Jiawei; Gao, Lei; Liu, Ying; Zuo, Kezhen; Zhao, Cuiping (Frontiers in Earth Science, 2023)
Current extensive seismicity in southern Sichuan Basin is ascribed to the reactivation of pre-existing faults, as a result of prolonged fluid injection for salt mining and shale gas development, respectively. However, the structural framework of the region remains poorly understood. Here, we apply Vp/Vs consistency-constrained double-difference seismic tomography to high quality phase data from 36,314 earthquakes jointly recorded by our local array and a regional seismic network to determine high-resolution velocity models. Earthquake relocations reveal shallow hypocenters for the Ms>5.0 earthquakes and two distinct seismogenic zones corresponding to the salt mine and shale gas regions, with most induced seismic events forming widespread lineaments some of which extend to the basement and are remarkably similar to the fault and fracture trends interpreted on reflection seismic and outcrops, respectively. Our 3-D crustal velocity analyses show that seismicity beneath the Changing salt mining area is associated with a combination of relatively low Vp/Vs (1.6-1.74) and high Vp/Vs (1.75-1.86) expressions, while most of small earthquakes within the Xingwen shale gas block are associated with relatively high Vp/Vs values (1.77-1.87), indicating the earthquakes in these two areas are caused by unique inducing mechanisms. The two moderately strong 2018 Xingwen Ms5.7 and 2019 Gongxian Ms5.3 earthquakes in the Xingwen shale gas block are located around low Vp/Vs zones, suggesting they could be structurally controlled. In comparison, the 2019 Changning Ms6.0 earthquake in the Changning salt mining area is associated with high Vp/Vs expression, suggesting its occurrence is related to fluid injections. In addition, top of the crystalline early Neoproterozoic (pre-Sinian) Sichuan basement is characterized by the 6.5 km/s Vp contour, which is new for earthquake tomographic studies in the region. Combined with outcrop analysis, we are able to construct a structural framework for induced seismicity in southern Sichuan basin, which unravels the structural architecture of induced seismicity.